Literature Study on the Development of Solar Power Plant (PLTS) Technology - Abdan fajrul Falah; Muhamad Lukman Hakim; Dr. Ikhwanul Qiram, S.T., M.T. (Journal of Educational Engineering and Environment, 2025)
The development of solar power plants (PLTS) has become a key focus in the global transition toward clean and sustainable energy, including in Indonesia. This study aims to examine the technological advancements in PLTS over the past decade, with an emphasis on solar panel efficiency, emerging technologies such as perovskite solar cells, and the challenges of implementing these systems within Indonesia’s geographic and socio-economic context. The methodology includes a systematic review of scientific articles from academic databases such as Google Scholar, Scopus, ScienceDirect, and ResearchGate, using inclusion criteria of peer-reviewed articles published between 2015 and 2025. The review reveals improvements in solar cell efficiency from first-generation technologies to perovskite innovations, alongside emerging trends in hybrid systems and the integration of PLTS with smart grids to enhance energy distribution reliability. The findings also highlight key barriers to PLTS implementation in Indonesia, including high initial investment costs, soiling losses, and limited infrastructure. This study recommends future research to focus on the development of high-efficiency systems, integrated energy storage solutions, climate-adaptive technology design for tropical environments, and the formulation of supportive policies to expand PLTS adoption in household, industrial, and remote area sectors